Is student digital competence shaped by schools or individual factors? - Ralph Hippe; Maciej Jakubowski (Publications Office of the European Union, 2022)
SELFIE for schools is a free online self-reflection tool which supports schools going digital. Its questionnaires ask school leaders, teachers and students about their opinions on the use of digital technologies for teaching and learning. In this paper, we examine whether digital competences of students vary more at the country, regional, school or individual level and what factors are associated with differences in competences at each level. The results show substantial variance at the school level but student digital competences are associated with other student-related factors, particularly digital infrastructure, pedagogy and assessments, and with school averages of these factors. Teacher-related variables are mostly insignificant and between-country differences are not important for the relationship between digital competences and other factors. Overall, the results show that individual level differences are the most important but composite peer effects also play a role in shaping digital competences.
Keywords: 370; Digitalisierung; Qualifikation; Schule; Selbstevaluation; EU-Staaten